Address given at the launching ceremony of the Eastern Caribbean Institute of Banking - Venner, K. Dwight (Eastern Caribbean Central Bank [Basseterre]KN, 1996)
Focuses on developments in banking and on the financial market in the Eastern Caribbean. Looks at the role of the Eastern Caribbean Institute of Banking